A cohort study on psychosocial adjustment and psychopathology in adolescents and young adults with congenital heart disease. Issue 1 (28th January 2013) - Freitas, Isabela Ribeiro; Castro, Marta; Sarmento, Sofia Lourenço; Moura, Cláudia; Viana, Victor; Areias, José Carlos; Areias, Maria Emília Guimarães
Abstract : Objectives: Our purpose was to study psychosocial adjustment and psychiatric morbidity of adolescents and young adults with congenital heart disease (CHD). Design: All assessment measures were obtained on a single occasion. Clinical data was obtained through the patient's clinical records. Setting: A teaching and tertiary care facility in Porto, Portugal. Participants: We evaluated 110 CHD patients (62 male) aged from 12 to 26 years (mean=18.00±3.617), 58 cyanotic. All assessment measures were obtained on a single occasion in a tertiary hospital. Demographic information and clinical history were collected. Primary and secondary outcome measures: Questionnaires regarded topics such as social support, family educational style, self-image and physical limitations, a standardised psychiatric interview Schedule for Affective Disorders and Schizophrenia—Lifetime version (SADS-L), and a self-report questionnaire on psychosocial adjustment, youth self-report or adult self-report. One of the relatives completed an observational version of the same questionnaire (child behaviour checklist (CBCL) or ABCL (adult behaviour checklist)). Results: We found a 21.8% lifetime prevalence of psychopathology, 31.3%, in females, 14.5% in males, showing a somewhat increased proneness in CHD patients. Females also showed worse psychosocial adjustment, with more somatic complaints (u=260 000; p=0.011), anxiety/depression (u=984 000; p=0.002), aggressive behaviour (u=920 500; p=0.001), attention problems (u=1123 500; p=0.027), thought problems (u=1069 500; p=0.010), internalisation (u=869 000; p=0.0) and externalisation (u=1163 000; p=0.05). Patients with severe CHD (u=939 000; p=0.03) and surgical repair (u=719 000; p=0.037) showed worse psychosocial adjustment. Those with poor social support showed more withdrawal (u=557 500; p=0.0) and social problems (u=748 500; p=0.023), and patients with unsatisfactory school performance revealed more anxiety/depression (u=916 000; p=0.02) and attention problems (u=861 500; p=0.007). Conclusions: CHD males with good social support and good academic performance have a better psychosocial adjustment.